Esensi Gaya Hidup Minimalis: Studi Living Qur’an Surah Al-Furqan ayat 67 Perspektif Generasi Milenial di Kota Medan - Riska Khairani; Saripuddin Saripuddin; Enny Fitriani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
The background of this research is the prevalence of unhealthy lifestyles among millennials lifestyles of extravagance wasting money flaunting wealth. Even though there are lifestyles that have a myriad of benefits when applied, they are none other than following a minimalist lifestyle. But sadly, minimalist life is not something that is coveted among millennials. In fact, in Surah Al-Furqan: 67 it is explained that we should not waste wealth excessively and should not be stingy with the assets we have. The formulation of the problem and the purpose of this study is to find out how contemporary classical scholars interpret Surah Al-Furqan: 67 and what is the essence of the minimalistic lifestyle according to millennials in Medan. The method used is phenomenology and interview qualitative method. The results of this study show the view of contemporary classical scholars that actually a minimalist lifestyle is that we can have and use it, but it is forbidden to overdo it. The nature of qanaah and zuhud really needs to be applied in living a lifestyle. Meanwhile, the application of a minimalist lifestyle in millennial society is still limited, because at the same time there are still many millennials who are competing to implement a hedonic lifestyle, but not a few are also starting to adopt a minimalist lifestyle by not following their passions to exaggerate in living life.